2020
DOI: 10.1101/2020.02.11.20021956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ophthalmologic evidence against the interpersonal transmission of 2019 novel coronavirus through conjunctiva

Abstract: 1 Background: The emerging 2019 novel coronavirus (2019-nCoV) has pushed several 2 countries into state of emergency all over the world. The possible transmission of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
225
2
22

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(260 citation statements)
references
References 16 publications
10
225
2
22
Order By: Relevance
“…The laboratory test revealed that the nasopharyngeal swab was positive while the conjunctival swab was negative. 5 On the contrary, our case All rights reserved. No reuse allowed without permission.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The laboratory test revealed that the nasopharyngeal swab was positive while the conjunctival swab was negative. 5 On the contrary, our case All rights reserved. No reuse allowed without permission.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent research has demonstrated that SARS-COV-2 can be detected in the conjunctival sac of patients with COVID-19 patients or suspected. 5 However, none of these patients had ocular symptoms. We therefore conducted a study to describe the clinical spectrum of ocular symptoms and laboratory test in conjunctival swab samples, we found a rare case of nosocomial SARS-COV-2 infection with conjunctivitis in a nurse, which suggests that ocular transmission may be a potential route of nosocomial transmission of the SARS-COV-2.…”
Section: Introductionmentioning
confidence: 92%
“…There were anecdotal reports suggesting that individuals may be infected by patients with subclinical infection [11], either by droplets or by direct contact with secretions from infected cases followed by subsequent inoculation into mucous membranes. Anecdotal reports suggested that when no eye protection was worn, the virus could also possibly be transmitted by aerosol contact with conjunctiva and cause infection [12][13][14]. Hence the close proximity between ophthalmologists and patients during slit lamp examination and direct ophthalmoscopy may pose an infectious risk to ophthalmologists.…”
Section: The Risks Of Covid-19 To Ophthalmologists and Patientsmentioning
confidence: 99%
“…Hence the close proximity between ophthalmologists and patients during slit lamp examination and direct ophthalmoscopy may pose an infectious risk to ophthalmologists. Ophthalmologists may also be caught off guard as conjunctivitis, though uncommon, could be the first presenting symptom of COVID-19, before the appearance of other symptoms such as cough and fever [12,13]. The American Academy of Ophthalmology has issued an alert advising ophthalmologists to wear masks and eye protection when seeing conjunctivitis patients with respiratory symptoms and history of international travel [14].…”
Section: The Risks Of Covid-19 To Ophthalmologists and Patientsmentioning
confidence: 99%
“…12 Latest investigation reveals that although SARS-CoV-2 (1 of 67 cases) was tested positive in the conjunctival sac of NCIP patients, the hypothesis is not supported. 13 Nevertheless, goggle is necessary to protect eyes for all medical workers.…”
Section: Vertical Transmission Is Another Important Mode Of Concernmentioning
confidence: 99%